PENGGUNAAN MEDIA BUSY BOOK GEOMETRI BAGI PERKEMBANGAN KOGNITIF PADA ANAK USIA 5-6 TAHUN DI TK BINA RABBANI MEDAN - Idzni Azhima; Larasati Nur Indah Prawesti; Meilina Juwita Andini; Khansa Nadhira Nazmi; Amanda Aulya; Jasmin Assyifa (HIBRUL ULAMA, 2025)
The National Council of Teachers of Mathematics (NCTM) states that one of the contents of mathematical concepts in early childhood is geometric shapes. In this study, busy book media was specifically designed with the aim of introducing the concept of geometric shapes. This study used a descriptive qualitative approach. Through the use of geometric busy book media, on the indicators of Mentioning and showing geometric shapes, both showed results of 73.33% of children in the Very Well Developing (BSB) category, 20% in the Developing According to Expectations (BSH) category, and 6.67% in the Starting to Develop (MB) category. Then on the indicator of arranging shapes from smallest to largest size and vice versa, showed results of 86.66% in the Very Well Developing (BSB) category, 6.67% in the Developing According to Expectations (BSH) and Starting to Develop (MB) category. On the indicator of the suitability of objects according to geometric shapes, the results were 86.66% of children in the Very Well Developing (BSB) category and 13.34% in the Developing According to Expectations (BSH) category. Meanwhile, in the simple data processing indicator, 66.67% of children were in the Very Well Developed (BSB) category and 33.37% of children were in the Developing According to Expectations (BSH) category. Based on the research results, it can be concluded that the use of geometry busy books can help introduce the concept of geometric shapes to children aged 5-6 years.